Ephedrine versus Phenylephrine Effect on Cerebral Blood Flow and Oxygen Consumption in Anesthetized Brain Tumor Patients: A Randomized Clinical Trial. (August 2020) - Koch, Klaus U.; Mikkelsen, Irene K.; Aanerud, Joel; Espelund, Ulrick S.; Tietze, Anna; Oettingen, Gorm v.; Juul, Niels; Nikolajsen, Lone; Østergaard, Leif; Rasmussen, Mads
Abstract : Background: Studies in anesthetized patients suggest that phenylephrine reduces regional cerebral oxygen saturation compared with ephedrine. The present study aimed to quantify the effects of phenylephrine and ephedrine on cerebral blood flow and cerebral metabolic rate of oxygen in brain tumor patients. The authors hypothesized that phenylephrine reduces cerebral metabolic rate of oxygen in selected brain regions compared with ephedrine. Methods: In this double-blinded, randomized clinical trial, 24 anesthetized patients with brain tumors were randomly assigned to ephedrine or phenylephrine treatment. Positron emission tomography measurements of cerebral blood flow and cerebral metabolic rate of oxygen in peritumoral and normal contralateral regions were performed before and during vasopressor infusion. The primary endpoint was between-group difference in cerebral metabolic rate of oxygen. Secondary endpoints included changes in cerebral blood flow, oxygen extraction fraction, and regional cerebral oxygen saturation. Results: Peritumoral mean ± SD cerebral metabolic rate of oxygen values before and after vasopressor (ephedrine, 67.0 ± 11.3 and 67.8 ± 25.7 μmol · 100 g −1 · min −1 ; phenylephrine, 68.2 ± 15.2 and 67.6 ± 18.0 μmol · 100 g −1 · min −1 ) showed no intergroup difference (difference [95% CI], 1.5 [−13.3 to 16.3] μmol · 100 g −1 · min −1 [ P = 0.839]). Corresponding contralateral hemisphere cerebral metabolic rate of oxygen values (ephedrine, 90.8 ± 15.9 and 94.6 ± 16.9 μmol · 100 g −1 · min −1 ; phenylephrine, 100.8 ± 20.7 and 96.4 ± 17.7 μmol · 100 g −1 · min −1 ) showed no intergroup difference (difference [95% CI], 8.2 [−2.0 to 18.5] μmol · 100 g −1 · min −1 [ P = 0.118]). Ephedrine significantly increased cerebral blood flow (difference [95% CI], 3.9 [0.7 to 7.0] ml · 100 g −1 · min −1 [ P = 0.019]) and regional cerebral oxygen saturation (difference [95% CI], 4 [1 to 8]% [ P = 0.024]) in the contralateral hemisphere compared to phenylephrine. The change in oxygen extraction fraction in both regions (peritumoral difference [95% CI], −0.6 [−14.7 to 13.6]% [ P = 0.934]; contralateral hemisphere difference [95% CI], −0.1 [− 12.1 to 12.0]% [ P = 0.989]) were comparable between groups. Conclusions: The cerebral metabolic rate of oxygen changes in peritumoral and normal contralateral regions were similar between ephedrine- and phenylephrine-treated patients. In the normal contralateral region, ephedrine was associated with an increase in cerebral blood flow and regional cerebral oxygen saturation compared with phenylephrine. Abstract : In adult patients with brain tumors, there were no differences in cerebral metabolic rate of oxygen in peritumoral regions or in the contralateral cerebral hemisphere after administration of ephedrine or phenylepherine.Supplemental Digital Content is available in the text.